INFLUENCE OF MOISTURE ON SOME ENGINEERING PROPERTIES OF BUSH MANGO SPECIES’ [Irvingia gabonensis AND Irvingia wombolu (HOOK, F.)] SEED AND KERNEL (2015)
Irvingia gabonensis and Irvingia wombolu are species of bush mango commonly found in Africa whose kernel are processed into soup. Literature generally abounds on the nutritional composition of the fruits and kernel but there is dearth of information on the engineering properties which are very important in the design of processing equipment and machines. This study was designed to investigate the influence of moisture on some engineering properties of seeds and kernels of I. gabonensis and I. wombolu. Irvingia gabonensis sourced from Oyo, Ogun, Osun and Irvingia wombolu sourced from Edo, Ondo and Imo states, Nigeria were used for the study. Based on moisture content at harvest and storage, their seeds were conditioned to moisture content of 10.0%, 20.0%, 30.0%, 40.0% and 50.0% and kernel to 2.2%, 3.7% and 5.3% (dry basis) using ASABE method.Properties studied include dimension, sphericity, true and bulk densities, porosity and angle of repose on commonly used material such as plywood, glass and steel for seed and kernel. Deformation, rupture force, failure stress, stiffness and Young’s moduli for seed were determined. Specific heat, thermal conductivity and diffussivity of kernel were studied. All properties were evaluated using ASABE standards and data analysed using ANOVA at p = 0.05. Kernel length, width, thickness and sphericity increased respectively from 25.9 to 30.4 mm, 15.7 to 19.2 mm, 3.5 to 4.3 mm and 43.3 to 44.6% with increase in moisture content. Length and width of seed decreased from 53.5 to 34.7 mm and 38.4 to 30.3 mm respectively with increase in moisture content while, thickness and sphericity increased from 3.5 to 4.2 mm and 66.7 to 78.0% respectively, indicating that seeds swell only in the lateral direction. Sphericity of seed was high indicating tendency to roll easily while low sphericity of kernel indicates sliding on structural surfaces. True density increased from 825.6 to 1216.4 kgm-3 and 697.7 to 1092.0 kgm-3 for seed, and kernel respectively. Their densities appear close to that of water hence may be difficult separating them using water. Angle of repose increased from 30.4 to 52.9o and 18.9 to 29.0o for seed and kernel respectively and was significantly affected by moisture content and species. Based on existing design, hopper and inclined discharge chute can be used for seed and flat bed for kernel. Deformation and Young’s modulus increased linearly from 1.4 to 3.9 mm and 5978.0 to 26098.0 Nmm-2 respectively for seed and were significantly affected by moisture and species. Specific heat and thermal conductivity of the two species increased with moisture and those of I. wombolu (982.8 JkgK-1, 0.2 Wm-1K-1) were significantly higher than I. gabonensis (795.9 JkgK-1, 0.1 Wm-1K-1) kernel. Thermal diffussivity also increased with moisture content and was significantly higher in I. wombolu than I.gabonensis; hence I. wombolu kernels will dry faster. Mechanical properties of the seeds evaluated at the selected moisture content showed that more energy would be required in cracking of Irvingiawombolu during kernel extraction than the same quantity of Irvingia gabonensis at the same processing condition.